Peningkatan Hasil Belajar: Efektivitas Model Project-Based Learning Pada Mata Pelajaran Instalasi Motor Listrik - Perdana, Wahyu Putra; Candra, Oriza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to determine the effectiveness of implementing the project-based learning model to improve the learning outcomes of class XI students in the Electric Motor Installation subject at SMK Negeri 5 Padang. This type of research uses the Pre-Experimental Design method and the research design used is One Group Pretest-Posttest using one class group. The subjects of this research were students of class XI TITL1 SMK Negeri 5 Padang for the 2024/2025 academic year, with a total of 28 students. Research instruments are tools used to collect data in research. The choice of research instruments depends on the type of data you want to collect. In this research, the research instruments used were pretest and posttest questions in objective form to evaluate student learning outcomes. Before research is carried out, the instrument must go through a trial phase. The data analysis technique used is a test of analysis prerequisites and effectiveness criteria. Based on data analysis of 28 students, the pretest results obtained a score of 14.30%. Meanwhile, the posttest score obtained an average score of 81.82. So the completeness of students' learning using the Project Learning learning model in the class XI TITL electric motor installation lesson at SMK 5 Negeri Padang has increased from the very low to high category.